2003
DOI: 10.1093/carcin/bgg107
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits phorbol ester-induced expression of cyclooxygenase-2 in mouse skin through suppression of extracellular signal-regulated kinase activity and NF- B activation

Abstract: Recently, there have been considerable efforts to search for naturally occurring substances for the intervention of carcinogenesis. Many components derived from dietary or medicinal plants have been found to possess substantial chemopreventive properties. Curcumin, a yellow coloring ingredient of turmeric (Curcuma longa L., Zingiberaceae), has been shown to inhibit experimental carcinogenesis and mutagenesis, but molecular mechanisms underlying its chemopreventive activities remain unclear. In the present work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
218
3
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(236 citation statements)
references
References 46 publications
11
218
3
4
Order By: Relevance
“…Curcumin was found to suppress COX-2 expression by inhibiting extracellular signal-regulated kinase (ERK) activity and NF-κB in phorbol ester-induced mouse skin tumorigenesis [26]. Curcumin has also been shown to induce growth arrest and apoptosis in various cancer cell lines [67,80,154,169].…”
Section: Pre-clinical and Clinical Trials Of Nf-κb Inhibitorsmentioning
confidence: 99%
“…Curcumin was found to suppress COX-2 expression by inhibiting extracellular signal-regulated kinase (ERK) activity and NF-κB in phorbol ester-induced mouse skin tumorigenesis [26]. Curcumin has also been shown to induce growth arrest and apoptosis in various cancer cell lines [67,80,154,169].…”
Section: Pre-clinical and Clinical Trials Of Nf-κb Inhibitorsmentioning
confidence: 99%
“…7,21 Equal amounts of protein extracts in RIPA lysis buffer [150 mM NaCl, 0.5% Triton X-100, 50 mM Tris-HCl (pH 7.4), 25 mM NaF, 20 mM EGTA, 1 mM DTT, 1 mM Na 3 VO 4 , and a protease-inhibitor-cocktail tablet] were subjected to 12% SDS-PAGE and electrophoretically transferred to nitrocellulose membrane. Protein bands were detected using an enhanced chemiluminescence detection kit.…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…21 An electrophoretic mobility shift assay (EMSA) was performed using a DNA-protein-binding detection kit (GIBCO BRL) for NFjB binding according to the Manufacturer's protocol as described previously. 21 Briefly, the NF-jB oligonucleotide probe (5 0 -AGT TGA GGG GAC TTT CCC AGG C-3 0 ) was labeled with [a-32 P]ATP by T4 polynucleotide kinase and purified on a Nick column.…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that curcumin-treated cells show the decreased expressions of COX-2 in various cell lines by inhibition of MAPKs signaling pathways (Chun et al, 2003;Hong et al, 2004;Kang et al, 2004). Currently, it is unknown whether curcumin modulates the expression of COX-2 in UVB-irradiated HaCaT cells.…”
Section: Introductionmentioning
confidence: 99%